Analysis of Factors Influencing Students' Digital Literacy in the Smart School Program at State Senior High School 13 Takalar - Samsi, Nur; Sahabuddin, Romansyah; Rahim, Abdul (Sean Institute, 2025)
This study aims to analyze the influence of internal factors in the form of curiosity, self-determination, and digital mindset on the level of digital literacy of students in the context of implementing the Smart School program at SMA Negeri 13 Takalar. Using a quantitative approach with descriptive and verification methods, data were obtained from 65 respondents through a Likert scale questionnaire. The results of the regression analysis showed that the three independent variables had a positive and significant effect on students' digital literacy. Self-determination was the factor with the largest contribution, followed by digital mindset and curiosity. The determination coefficient of 75.9% indicates that most of the variation in digital literacy can be explained by these three variables. This finding emphasizes the importance of students' psychological readiness, not only the provision of technological infrastructure, in supporting digital learning. The implications of this study indicate the need for learning strategies that focus on developing students' character and internal competencies so that the transformation of digital education can run optimally